A Comprehensive Review of the Impact of Family Cohesion, Religious Values, and Spiritual Intelligence on Youth Susceptibility to Addiction - Moazami Goudarzi, Soheil; Azemoudeh, Masoumeh; Hoseini Nasab, Seyyed Davoud (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aims to explore the impact of spiritual intelligence and family cohesion on youth addiction prevention. Methods: A comprehensive review of the literature was conducted using peer-reviewed journal articles, books, and authoritative reports published between 2000 and 2024. Databases such as PubMed, PsycINFO, Scopus, and Google Scholar were searched using keywords related to spiritual intelligence, family cohesion, and youth addiction. Inclusion criteria focused on studies examining the relationship between these variables and their role in substance abuse prevention among adolescents and young adults. Findings: The review identified several protective mechanisms through which spiritual intelligence contributes to resilience, such as self-awareness, moral integrity, and emotional regulation. Similarly, family cohesion, characterized by effective communication, emotional support, and strong parental bonds, was found to significantly reduce the risk of substance abuse in youth. An interactive effect was observed, where spiritual intelligence and family dynamics together enhanced adolescents’ ability to cope with stress and peer pressure, minimizing the likelihood of engaging in addictive behaviors. Conclusion: Spiritual intelligence and family cohesion are crucial protective factors in preventing youth addiction. Early interventions that focus on fostering spiritual intelligence and strengthening family relationships can effectively reduce addiction risk. The article emphasizes the need for educational programs and community-based initiatives to promote these protective factors from adolescence.